2013
DOI: 10.17221/6941-cjas
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lutein, spray-dried Chlorella, and synthetic carotenoids effects on yolk colour, oxidative stability, and reproductive performance of laying hens

Abstract: ISA Brown hens were fed diets supplemented with the synthetic carotenoids Carophyll Red and Carophyll Yellow at 20 and 15 mg/kg, respectively, lutein at 250 mg/kg, and the algae Chlorella at 12.5 g/kg. The synthetic carotenoids, lutein, and Chlorella significantly increased egg weight (P < 0.001), shell weight (P < 0.001), and thickness (P = 0.017) and decreased the yolk/albumen ratio (P = 0.035) of the eggs. Lutein but not the Carophylls or Chlorella significantly increased the shell br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 17 publications
4
51
0
2
Order By: Relevance
“…The results are in agreement with the findings of Englmaierova et al (2013) who reported that feeding diets supplemented with synthetic carotenoids such as lutein significantly increased the egg production of Isa Brown hens. Moreover Hasanuzzaman et al (2012) detected higher egg production and egg weight in the treatment groups of layers fed with diets of 6.5% and 13% sea buckthorn cake compared to the control group of layers.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The results are in agreement with the findings of Englmaierova et al (2013) who reported that feeding diets supplemented with synthetic carotenoids such as lutein significantly increased the egg production of Isa Brown hens. Moreover Hasanuzzaman et al (2012) detected higher egg production and egg weight in the treatment groups of layers fed with diets of 6.5% and 13% sea buckthorn cake compared to the control group of layers.…”
Section: Resultssupporting
confidence: 92%
“…Also, the mortality reasons (diseases of the genitals, metabolic disorders and cannibalism) of the hens were not affected by diet with 5% sea buckthorn fruit residues. These results are in concordance with the study of Englmaierova et al (2013) who indicated that Isa Brown hens that were fed diets supplemented with synthetic carotenoids such as lutein did not differ in terms of mortality (%) compared with the control group. Moreover, Hasanuzzaman et al (2012) reported that the mortality of birds was not affected by different levels of sea buckthorn.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…After completing the physical measurements, shells were analyzed for calcium, phosphorus, magnesium, and zinc content. Calcium and phosphorus were determined by a method described by Englmaierova et al (2013). AOAC (2005) procedures were used to determine CP, magnesium, and zinc in feed mixtures and egg shells.…”
Section: Methodsmentioning
confidence: 99%